2012
DOI: 10.1136/injuryprev-2012-040601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social and technological distraction on pedestrian crossing behaviour: an observational study

Abstract: ObjectivesThe objective of the present work was to study the impact of technological and social distraction on cautionary behaviours and crossing times in pedestrians.MethodsPedestrians were observed at 20 high-risk intersections during 1 of 3 randomly assigned time windows in 2012. Observers recorded demographic and behavioural information, including use of a mobile device (talking on the phone, text messaging, or listening to music). We examined the association between distraction and crossing behaviours, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
159
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(181 citation statements)
references
References 21 publications
18
159
2
2
Order By: Relevance
“…For example, problematic smartphone use is related to traffic accidents (Cazzulino, Burke, Muller, Arbogast, & Upperman, 2014;Thompson, Rivara, Ayyagari, & Ebel, 2013), shoulder and neck problems (Shan et al, 2013;Xie, Szeto, Dai, & Madeleine, 2016), sleep impairment (Demirci, Akgonul, & Akpinar, 2015;Eyvazlou, Zarei, Rahimi, & Abazari, 2016), academic problems (Seo, Park, Kim, & Park, 2016), and poor physical fitness (Rebold, Sheehan, Dirlam, Maldonado, & O'Donnell, 2016). Furthermore, problematic smartphone use is related to mental health problems such as anxiety and depression (reviewed in .…”
Section: Introductionmentioning
confidence: 99%
“…For example, problematic smartphone use is related to traffic accidents (Cazzulino, Burke, Muller, Arbogast, & Upperman, 2014;Thompson, Rivara, Ayyagari, & Ebel, 2013), shoulder and neck problems (Shan et al, 2013;Xie, Szeto, Dai, & Madeleine, 2016), sleep impairment (Demirci, Akgonul, & Akpinar, 2015;Eyvazlou, Zarei, Rahimi, & Abazari, 2016), academic problems (Seo, Park, Kim, & Park, 2016), and poor physical fitness (Rebold, Sheehan, Dirlam, Maldonado, & O'Donnell, 2016). Furthermore, problematic smartphone use is related to mental health problems such as anxiety and depression (reviewed in .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Parental use of mobile devices in playgrounds, restaurants, or other public venues with children has received criticism in the lay press, 4,5 with concern that parental distraction by these devices may affect child safety or emotional well-being. Studies have demonstrated unsafe driving 6 and pedestrian behavior 7 while people are distracted by mobile devices, but the ways in which devices are being used around children, and the parenting behaviors associated with such use, have not been investigated.…”
mentioning
confidence: 99%
“…The analysis found that pedestrians who were text messaging took over half a second longer to cross each lane (0.55 s, 95% CI 0.36 to 0.75) and pedestrians who were listening to music walked faster than undistracted pedestrians by an average of 0.16s per lane. Thompson et al (2013) also examined the association between whether or not pedestrians looked both ways and pedestrian distractions, adjusted for age and gender. The results revealed that some distractions were associated with risky pedestrian behaviors, with text messaging appearing particularly risky.…”
Section: Naturalistic Observationmentioning
confidence: 99%
“…• Using a fixed interval selection procedure, Thompson et al (2013) found that texting pedestrians took over a half-second longer to cross each lane than non-distracted pedestrians.…”
Section: Naturalistic Observation Summarymentioning
confidence: 99%